PENGARUH KUALITAS PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SHUTTLECOCK MEREK YUNDA DENGAN CITRA MEREK SEBAGAI VARIABEL MODERATING - Nanda Kristanto, Erni Widajanti & Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
In the current era of globalization, every craftsman or a small entrepreneur has tobe able to compete with big businesses improve consumer purchasing decisions, as wellas craftsmen shuttlecock in Pringgolayan Tipes Surakarta, in an effort to increase thepurchasing decisions of consumers by improving product quality, create word of mouthand maintaining brand image. The purpose of this study was to analyze the significanceof the influence of product quality, word of mouth and brand image of the brandpurchase decision Shuttlecock Shuttlecock Yunda on Consumers in the Craftsman HomeIndustry in Pringgolayan Tipes Surakarta. Analyzing the moderating effects of brandimage on the influence of product quality and word of mouth to the purchasing decisionat the Consumer Shuttlecock in Craftsmen Home Industry in Pringgolayan TipesSurakarta. This study uses survey method, the type of data used quantitative andqualitative data, the data source used primary data and secondary data. Population andsample in this study are all consumers Shuttlecock in Craftsmen Home Industry inPringgolayan Tipes Surakarta, the number of samples used in this study were 100respondents to the sampling technique uses accidental sampling. Data collectionmethods are used: questionnaires and documentation. Data analysis technique used totest the validity, reliability test, classic assumption test and multiple linear regressionanalysis, t-test, F, coefficient determination and test the absolute difference. Inconclusion that: no significant effect the quality of products on purchase decisionsshuttlecock brand Yunda, there was a significant effect of word of mouth on purchasedecisions shuttlecock brand Yunda, no significant effect of brand image on purchasedecisions shuttlecock brand Yunda, brand image moderating influence the variablequality of the products on purchase decisions shuttlecock Yunda brand, brand imagedoes not moderate the effect of variable word of mouth on purchase decisions Yundabrand shuttlecock.Keywords: product quality, word of mouth, brand image, purchasing decisions